2020
DOI: 10.1002/oby.22913
|View full text |Cite
|
Sign up to set email alerts
|

Severe Obesity as an Independent Risk Factor for COVID‐19 Mortality in Hospitalized Patients Younger than 50

Abstract: Objective Coronavirus disease 2019 (COVID‐19) continues to spread, and younger patients are also being critically affected. This study analyzed obesity as an independent risk factor for mortality in hospitalized patients younger than 50. Methods This study retrospectively analyzed data of patients with COVID‐19 who were hospitalized to a large academic hospital system in New York City between March 1, 2020, and May 17, 2020. Data included demographics, comorbidities, BMI, and smoking status. Obesity groups inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
240
7
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(279 citation statements)
references
References 12 publications
16
240
7
16
Order By: Relevance
“…Obesity has been reported as an independent risk and prognostic factor for the disease severity and the requirement of advanced medical care in COVID-19 [ 18 ]. Klang et al concluded that morbid obesity is an independent risk factor for mortality of COVID-19 in hospitalized patients under the age of 50 years [ 19 ], the same age range as our study. Obesity can restrict ventilation by impeding diaphragm excursion and reducing protective cardiorespiratory reserve.…”
Section: Discussionsupporting
confidence: 72%
“…Obesity has been reported as an independent risk and prognostic factor for the disease severity and the requirement of advanced medical care in COVID-19 [ 18 ]. Klang et al concluded that morbid obesity is an independent risk factor for mortality of COVID-19 in hospitalized patients under the age of 50 years [ 19 ], the same age range as our study. Obesity can restrict ventilation by impeding diaphragm excursion and reducing protective cardiorespiratory reserve.…”
Section: Discussionsupporting
confidence: 72%
“…Risk factors that have been identified in prior studies include older age, male sex, hypertension, diabetes, chronic obstructive pulmonary disease, cardiac disease, liver disease, chronic kidney disease, neurologic disorders, cancer, obesity, higher overall burden of comorbidity, and smoking. 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors for developing severe COVID-19 disease have been reported, including sociodemographic factors and comorbid conditions. 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 However, most prior studies, particularly those published earlier in the course of the pandemic, did not include multivariable adjustment to identify independent risk factors, and few studies examined a range of different disease outcomes, including hospitalization, mechanical ventilation, and death. Most prior studies have been local or regional, rather than national, in scope.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that obesity may be a very signi cant consideration in younger people [32][33][34] . A report of 3,615 New York patients revealed that obesity was strongly correlated with hospital and ICU admittance for patients under 60 years of age 32 .…”
Section: Discussionmentioning
confidence: 99%